Enhanced Myc Expression in Silkworm Silk Gland Promotes DNA Replication and Silk Production - Wenliang Qian; Yan Yang; Zheng Li; Yuting Wu; Xuechuan He; Hao Li; Daojun Cheng (Insects, 2021)
Silkworm is an economically important insect that synthetizes silk proteins for silk production in silk gland, and silk gland cells undergo endoreplication during larval period. Transcription factor Myc is essential for cell growth and proliferation. Although silkworm Myc gene has been identified previously, its biological functions in silkworm silk gland are still largely unknown. In this study, we examined whether enhanced Myc expression in silk gland could facilitate cell growth and silk production. Based on a transgenic approach, Myc was driven by the promoter of the fibroin heavy chain (FibH) gene to be successfully overexpressed in posterior silk gland. Enhanced Myc expression in the PSG elevated FibH expression by about 20% compared to the control, and also increased the weight and shell rate of the cocoon shell. Further investigation confirmed that Myc overexpression increased nucleus size and DNA content of the PSG cells by promoting the transcription of the genes involved in DNA replication. Therefore, we conclude that enhanced Myc expression promotes DNA replication and silk protein expression in endoreplicating silk gland cells, which subsequently raises silk yield.